Comparing the Responses of Patients with Osteoarthritis to Some Pharmacological and Non-Pharmacological Treatment Modalities, Cross Sectional Survey - Sahar El-Ashmony (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Osteoarthritis (OA) is the most common form of arthritis, and is a leading cause of disability among older adults. Many different therapeutic strategies are used in OA management including both pharmacological and non-pharmacological modalities with various patient responses. However, a perfect therapy for OAis still to be found.This research aims to compare the degree of pain improvement in osteoarthritic patients in response to various treatment modalities through an online questionnaire. Methods: This descriptive cross-sectional study was conducted in January 2020 in Makkah, Saudi Arabia, and Cairo, Egypt. The total sample obtained was 1,870 residents with OA. A computer-based survey of osteoarthritis was conducted electronically. Results: The highest age range of participants was between 41-50 years (65%). More than two-thirds (1210) were females.The knee is significantly (P<0.005) the most common joint affected followed by back and neck.Concerning the treatment modalities asked in the questionnaire; physical/hydrotherapy, joint injection, and paracetamol are significantly (P<0.005) the most commonly used by participants.The number of participants those indicates the highest responses to pain improvement (50 % and more) to paracetamol, glucosamine/chondroitin, nutritional supplements, and antioxidants were significantly (P<0.005) more than those for other treatment modalitiesConclusion: The most commonly used treatment methods for osteoarthritic pain were physiotherapy/hydrotherapy, joint injection, and oral paracetamol. Those who have achieved the highest response regarding pain improvement were paracetamol, antioxidants, glucosamine / chondroitin, and nutritional supplements.